2010
DOI: 10.1177/0960327110368415
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of vitamin C on chronic chlorpyrifos-induced erythrocyte osmotic fragility in Wistar rats

Abstract: Chronic exposure to chlorpyrifos (CPF) has been shown to cause increased lipoperoxidative changes in the erythrocyte membranes. The relationship between chronic CPF-induced lipoperoxidative changes and erythrocyte fragility has not been elucidated. The aim of the present study is to evaluate the role of lipoperoxidation on CPF-induced erythrocyte fragility and the ameliorative effect of vitamin C. Twenty animals divided at random into four groups of five animals each served as subject for this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 17 publications
5
51
1
Order By: Relevance
“…This confirms the increase in MDA concentration following CPF exposure in previous studies [18][19][20][21][22][23]35] . MDA is a lipoperoxidation by-product resulting from interaction of oxygen radicals with polyunsaturated fatty acids residues in membrane phospholipids and has been shown to damage proteins and DNA [36] .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This confirms the increase in MDA concentration following CPF exposure in previous studies [18][19][20][21][22][23]35] . MDA is a lipoperoxidation by-product resulting from interaction of oxygen radicals with polyunsaturated fatty acids residues in membrane phospholipids and has been shown to damage proteins and DNA [36] .…”
Section: Discussionsupporting
confidence: 90%
“…However, toxicity has been reported at doses that do not inhibit AChE [14,15] . Therefore, other mechanisms including the induction of oxidative stress have been implicated in CPF-induced toxicity [16][17][18][19][20][21][22][23] . During oxidative stress, the body's antioxidant mechanisms are overwhelmed by the oxidants, resulting in cellular damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, low osmotic resistance leads to intravascular haemolysis, which reduces the number of erythrocytes, hence leading to anaemia (Wu et al 1998) if not treated. EOF has also been used as an indicator of oxidative stress in animals (Adenkola and Ayo 2009;Wahab et al 2010;Ambali et al 2010). Although the above studies demonstrated differences in EOF within and between species under various conditions, comparisons of normal EOF between the Nigerian indigenous breed of dog and exotic breeds have not been reported.…”
Section: Introductionmentioning
confidence: 92%
“…Zinc, a divalent cation with manifold biochemical and physiological functions, may play principal neuromodulatory roles in the central nervous system. Indeed, zinc is co-released with glutamate, and it modulates glutamatergic excitation by inhibiting N-methyl-D-aspartate (NMDA) receptors, and averts gammaaminobutyric acid (GABA) inhibition by blocking GABA-A receptor function [30,31] reported that zinc exerts its antioxidant property in ameliorating the effect of chlorpyrifos-induced erythrocyte fragility in Wistar rats. Neuropsychological performance has been reported to improve with Zn supplementation in young Chinese children, especially when other micronutrient nutrition is sufficient [27,28].…”
Section: Insights In Biomedicine Issn 2572-5610mentioning
confidence: 99%